The Social Inequality Portrayed on Bong Joon Ho’s Parasite Movie - Nurmala Dewi; Amelia Amelia; Tati Mardewi; Furi Indriyani (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
This study aims to analyze the social inequality portrayed in the Parasit movie directed by Bong Joon Ho. For research method, a qualitative approach is chosen to be applied which is content analysis as research design. In collecting the data, the writers use the Parasite movie as an object of the research, and search a lot of references from the internet and libraries to support the theories as baselines of analysis. Parasite movie depicts the two families’ lives, Park's family and Kim's family, where the social conditions and the daily lifestyles are very contrastive; the first family is rich and wealth and the later one is poor and deprivation. These social inequalities reflect a social phenomenon in the real world which becomes the motives for fraudulent and greedy character and gradually leads to criminal actions. The gaps between both families are demonstrated in some aspects, such as economy and work, education, house, food, and fashion. And the disparities shown by those elements indicate where the social class they belong and what the impact to their life.